WOMEN AND MALAYSIAN POLITICS: CHALLENGES AS MEDIATORS IN POLITICAL LEADERSHIP - Niza Tan Mohd Aminuddin; Shakirah Noor Azlan (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Effective governance in a democratic country needs the leadership of qualified people, who have acquired knowledge and experience to lead a nation. On this backdrop, the governance should strive to ensure that the political leaders to be selected are not just competent but able to exercise leadership in an inclusive way. However, in Malaysia, gender bias has been an issue that has raged on, particularly during the phases of elections, where women are considered to face numerous challenges with regard to political leadership. This paper explores the main challenges that women encounter as mediators in political leadership within Malaysia’s democratic governance. The research highlights that women in Malaysian politics have to meet substantial obstacles relating to gender disparities, bias and discrimination, media stereotyping, and balancing family responsibilities against their political careers. Societal norms generally depict women as fit for domestic duties but not for national leadership, thus giving people the beliefs that gender equality is relevant within, but not outside, the domestic sphere. Because of deep-seated stereotypes and indirect forms of discrimination, the end results have been low self-esteem and motivation among women with the aspirations to take up leadership roles. In that regard, implementation of empowerment initiatives, gender equality measures, and comprehensive legislations should be considered to break these barriers that challenge women’s participation in political leadership, hence challenging the deep-rooted practices and norms categorizing them as subordinate to men in political positions.